Effects of work-family conflict on turnover intention among primary medical staff in Huaihai Economic Zone: a mediation model through burnout - Wen, Zongliang; Xu, Jintao; Yu, Jinxun; Huang, Xiaojing; Ni, Yuting (Frontiers in Psychiatry, 2023)
Background: How medical personnel manage conflicts between work and family is a problem that countries around the world are facing. Especially after the challenge of the COVID-19 epidemic, it is necessary to explore the possible mechanism of work-family conflict, burnout and turnover intention among primary medical staff.Objectives: This study aims to observe the turnover intention of Chinese primary medical staff and explore the relationship between work-family conflict, burnout, and turnover intention. Methods: A cross-sectional study included turnover intention questionnaire, Maslach Burnout Scale general scale (MBI-GS) and Work-Family Conflict Scale (WFCS) to understand the turnover intention, burnout and work-family conflict among primary medical staff in four cities (Xuzhou,Linyi,Huaibei and Shangqiu cities) within the Huaihai Economic Zone. Spearman correlation analysis and hierarchical multiple regression analysis were used to examine the related factors of turnover intention. Structural equation modeling (SEM) was used to study the mediating role of burnout between work-family conflict and turnover intention.Results: In this study, there is a positive correlation between work family conflict and turnover intention (P<0.01). Demographic characteristics, work-family conflict, and burnout explained 2.3, 20.3, and 8.8% of the incremental variances, respectively. Burnout mediated the association between work-family conflict and turnover intention.Conclusions: Burnout can be regarded as a mediator between two different variables: work-family conflict and turnover intention. The improvement in work-family conflict and the alleviation of burnout may play a key role in reducing the willingness of primary medical staff to resign.